2023
DOI: 10.3201/eid2908.230528
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Orientia spp. Bacteria in Field-Collected Free-Living Eutrombicula Chigger Mites, United States

Abstract: Scrub typhus, a rickettsial disease caused by Orientia spp., is transmitted by infected larval trombiculid mites (chiggers). We report the molecular detection of Orientia species in free-living Eutrombicula chiggers collected in an area in North Carolina, USA, to which spotted fever group rickettsiae infections are endemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Recent studies have identified scrub typhus in areas previously believed to be free of this disease, including South America and Africa [5,6]. In 2023, the molecular detection of Orientia species was reported, for the first time, in free-living Eutrombicula chiggers collected in North Carolina [7], which highlights the concerning potential of human illness related to Ot infection in the United States. At present, no effective vaccines are available for scrub typhus, partly due to the antigenic diversity among various Ot strains and undefined roles of host immune responses in controlling or promoting the infection [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified scrub typhus in areas previously believed to be free of this disease, including South America and Africa [5,6]. In 2023, the molecular detection of Orientia species was reported, for the first time, in free-living Eutrombicula chiggers collected in North Carolina [7], which highlights the concerning potential of human illness related to Ot infection in the United States. At present, no effective vaccines are available for scrub typhus, partly due to the antigenic diversity among various Ot strains and undefined roles of host immune responses in controlling or promoting the infection [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…On the opposite side of the world Orientia tsutsugamuschi causes >1 million cases a year of scrub thyphus transmitted by chiggers, which is found primarily in southeast Asia but has an expanding territory and where the emergence of antibiotic-resistant strains is a significant concern ( Luce-Fedrow et al., 2018 ). Recently, O. tsutsugamuschi was found in chiggers in North Carolina, indicating their presence in the USA, although the spread of disease has not occurred to date ( Chen et al., 2023 ). The rise of infections and expansion of vector territories for these obligate intracellular bacteria are making them a rising public health concern.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Locally acquired cases in Africa, the Middle East, and South America and detection of Orientia species in mites in the United States signify scrub typhus as a globally emerging health threat. 10-17 O. tsutsugamushi infects leukocytes at the mite feeding site and disseminates to invade endothelial cells of multiple organs. 18,19 Acute scrub typhus symptoms are non-specific and include fever, rash, headache, and lymphadenopathy.…”
Section: Introductionmentioning
confidence: 99%